(untitled) (Grande Medical Journal, 2025)
Background Anderson Hynes dismembered pyeloplasty is the gold standard procedure for management of Pelvic Ureteric Junction Obstruction (PUJO) in children with success rate of 90-95%. The aim of the current study is to evaluate safety, efficacy and outcomes of Anderson Hynes Pyeloplasty in our part of the world. Method A retrospective study was conducted involving 69 children who underwent Open Anderson Hyne’S dismembered Pyeoplasty over a period of 2 years from March 2022 to April 2024. Patient were evaluated with respect to age, sex, ultrasonographic grading of hydronephrosis, affected side, operation time, postoperative complications and follow-up outcomes and analyzed. Result This study consisted of 69 patients with moderate to severe hydronpehrosis secondary to PUJO underwent open pyeloplasty. Male-female ratio was 2:1. Average mean age was 41.67 months (1 month to 156 months) where 28 patients (40.57%) were infants. 45 patients (65.2%) had grade 3 hydronephrosis whereas 24 patients (34.8%) had grade 4 hydronephrosis in ultrasound abdomen. Right sided pyeloplasty was performed in 48 children (69.6%) and left sided was performed in 21 children (30.4%). Mean operative time period was 92.5 minutes with mean hospital stay of 3.53 days (3 days to 5 days). Post-pyeloplasty, 63 patients (91.3%) showed improvement in ipsilateral kidney function on DTPA scan and three patient developed anastomotic stricture which required Re-do Pyeloplasty. Conclusion Anderson Hyne’s dismembered pyeloplasty has shown better outcome amongst pediatric patient with PUJO. It has a high success rate with significant improvement in kidney drainage function.